Biodiversity and Ecophysiology of Yeasts - Rosa, Carlos Augusto; Peter, Gabor; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
In the last few decades more and more yeast habitats that were not investigated earlier, spanning cold climates to tropical regions and dry deserts to rainforests, have been explored. As a result, a large body of ecological data has been accumulated and the number of known yeast species has increased rapidly. This book provides an overview of the biodiversity of yeasts in different habitats. The recent advances achieved by the application of molecular biological methods in the field of yeast taxonomy and ecology are also incorporated in the book. Wherever possible, the interaction between yeasts and the surrounding environment is discussed.
Yeast Biodiversity: How Many and How Much? -- Yeast Systematics and Phylogeny — Implications of Molecular Identification Methods for Studies in Ecology -- Yeast Biodiversity and Culture Collections -- Genomics and Biodiversity in Yeasts -- Methods for Investigating Yeast Biodiversity -- Sugar Metabolism in Yeasts: an Overview of Aerobic and Anaerobic Glucose Catabolism -- Diversity of Nitrogen Metabolism Among Yeast Species: Regulatory and Evolutionary Aspects -- Environmental Factors Influencing Yeasts -- Yeast Responses to Stresses -- Antagonistic Interactions Among Yeasts -- Yeasts in Soil -- Yeast Biodiversity in Freshwater, Marine and Deep-Sea Environments -- Phylloplane Yeasts -- Yeast and Invertebrate Associations -- Yeasts in Extreme Environments -- Yeast Biodiversity in the Antarctic -- Yeast Biodiversity in Tropical Forests of Asia -- Yeast Communities in Tropical Rain Forests in Brazil and other South American Ecosystems -- The Biogeographic Diversity of Cactophilic Yeasts -- Black Yeasts and Meristematic Fungi: Ecology, Diversity and Identification -- Yeasts as Indicators of Environmental Quality -- Yeast Biodiversity and Biotechnology.
Keywords: Microbiology; Biodiversity; Microbial ecology; Microbial genetics; Microbial genomics; Biotechnology; Microbiology; Biodiversity; Microbial Ecology; Microbial Genetics and Genomics; Biotechnology